Aplasia Cutis Congenita: Review of 29 Cases and Proposal of a Therapeutic Strategy - Maillet-Declerck, Marie; Vinchon, Matthieu; Guerreschi, Pierre; Pasquesoone, Louise; Dhellemmes, Patrick; Duquennoy-Martinot, Véronique; Pellerin, Philippe (European Journal of Pediatric Surgery, 2013)
Introduction Aplasia cutis congenita (ACC) is a rare congenital disorder, which most commonly involves the scalp, and can affect the galea, the pericranium, the bone, and the dura mater. ACC thus is at risk of infection and hemorrhage. There is no consensus over the ideal management and the role for plastic surgery.Materials and Methods We reviewed retrospectively our experience with 29 patients treated between 1976 and 2011.Results The patients were 17 male and 12 female, 25 being referred immediately at birth. The size of the defect ranged from 1 to 192 cm2. Thirteen patients had bone aplasia. Initial conservative treatment was decided in five cases; 15 patients underwent excision–sutures with or without local plasty, 8 underwent pedicled scalp flap, and 1 had skin graft followed by further reconstruction by a free flap. Four patients died in neonatal period because of infection or associated ailments. All others patients achieved complete healing.Discussion The mortality rate of ACC remains high and increases with the size of bone defect. We propose a therapeutic strategy based on the size of the skin defect and the nature of underlying exposed structures. Cranioplasty is exceptionally necessary because of good spontaneous bone regeneration within few months or years. Cosmetic appearance can be improved later by skin expansion.Conclusion Aplasia cutis congenita is a rare malformation with sometimes a rapid fatal issue. A precise evaluation of surface and depth of the lesion is essential to decide if and how to operate, in order to provide rapid and efficient coverage.
Keywords: aplasia cutis congenita; scalp flap; congenital scalp and skull defect; vertex